Developing an electronic student worksheet with process differentiation for the chemical kinetics topic - Magtar, Catarina Pasriana; Pamenang, Fransisca Ditawati Nur (Proceedings of International Conference on Research in Education, 2025)
This study develops and evaluates an electronic student worksheet with process differentiation for the topic of chemical kinetics. It is motivated by students' difficulties in understanding the complex concepts of chemical kinetics and the persistence of conventional teaching methods. The worksheet was developed using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation) and tested on 21 eleventh-grade high school students. Data were analyzed through N-Gain calculations and response percentages. The results indicate that the worksheet meets the feasibility criteria. Expert validation showed that the worksheet is highly feasible, with average scores of 92% for content, 88.8% for activities, 95% for appearance and visuals, and 93.3% for language, resulting in an overall average of 92.4%. Practicality was confirmed by students’ high positive responses, who strongly agreed that the worksheet was engaging and easy to use. Effectiveness was demonstrated through N-Gain analysis, with improvements in learning outcomes for auditory (0.64), visual (0.69), and kinesthetic (0.68) learners, all categorized as “Medium.” Thus, the student worksheet is proven effective, practical, and feasible for improving learning outcomes in chemical kinetics, offering an innovative alternative learning resource that accommodates diverse student characteristics.
Keywords: chemical kinetics; electronic student worksheets; process differentiation